Low-power photodetectors based on PVA-modified reduced graphene oxide hybrid solutions - Shih, Yi-Shan (2022)
Photodetectors based on reduced graphene oxide (rGO) have attracted much attention owing to their simple and low-cost fabrication process. However, the aggregation and defects of rGO flakes still limit the performance of rGO photodetectors. Controlling the composition of rGO has become a vital factor for its prospective applications. For example, the interconnection between rGO and polymers for modified morphologies of rGO films leads to an enhanced performance of devices. In this work, a practical approach to engineer surface uniformity and enhance the performance of a photodetector by modifying the rGO film with hydrophilic polymers poly(vinyl alcohol) (PVA) is reported. Compared with the rGO photodetector, the on/off ratio for the PVA/rGO photodetector shows 3.5 times improvement, and the detectivity shows 53% enhancement even when the photodetector is operated at a low bias of 0.3 V. This study provides an effective route to realize PVA/rGO photodetectors with a low-power operation which shows promising opportunities for the future development of green systems.